2020
DOI: 10.3389/fpsyg.2020.01533
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Validation of Nonlinear Postural Predictors of Visually Induced Motion Sickness

Abstract: Virtual reality (VR) technology has become increasingly prevalent in our society and has been used for a myriad of applications ranging from psychotherapy to training members of the military. However, one issue that arises from the use of VR is motion sickness, thus making predictors and indicators of motion sickness desirable. To date, a number of indicators of motion sickness have been derived based on nonlinear characteristics of human motion recorded using motion capture systems. While it is known that non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…It was found that the well participants that were incorrectly flagged as sick tended to be flagged only in their later trials. This is consistent with previous work that demonstrates that postural instability emerges over time even in well participants (Koslucher, et al, 2016; Smart et al, 2002; 2007; Teaford et al, 2020; Villard et al, 2008). See Figure 3 for a graphic depicting the mean slope values (i.e.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that the well participants that were incorrectly flagged as sick tended to be flagged only in their later trials. This is consistent with previous work that demonstrates that postural instability emerges over time even in well participants (Koslucher, et al, 2016; Smart et al, 2002; 2007; Teaford et al, 2020; Villard et al, 2008). See Figure 3 for a graphic depicting the mean slope values (i.e.…”
Section: Resultssupporting
confidence: 93%
“…Ideally, a motion sickness prediction algorithm for the consumer setting would utilize data already being collected by the virtual device; thus, negating the need for additional specialized equipment as well as minimizing the additional computational load on the computer. Specifically, many current virtual devices track motion/position of the user that we argue could be utilized to make predictions about behavioral/physiological states (Teaford et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simeonov used virtual reality (VR) technology to simulate walking on a roof plank and observed the effect of height on the lateral angular velocities of the trunk and rearfoot [ 28 ]. Motion sickness caused by VR technology could be confused with the effect of path height and width on walking [ 29 , 30 ]. The effects of narrow and wide path width on the trunk and joint kinematics have been compared [ 27 , 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the sensory conflict theory, a mismatch between the information delivered by the visual, vestibular, and/or somatosensory system that is not in accordance with the movement predicted by a cortical, internal model is the primary cause for motion sickness [2 ▪▪ ]. In contrast, the postural instability theory claims that changes in one's ability to control posture and balance are the primary cause for motion sickness, preceding the onset of symptoms [9,10]. The latter theory has generated controversy as well controlled studies failed to find a relationship between postural control and motion sickness [11 ▪ ].…”
Section: Theoretical Considerations and Related Phenomenamentioning
confidence: 99%